Promosi Kesehatan Tentang Hipertensi di Puskesmas Pekauman Kota Banjarmasin - Kirana, Rita; Januarsih; Maulida, Anggi Safira; Rachmadi, Agus (JURNAL PENGABDIAN KEPADA MASYARAKAT SISTHANA, 2023)
The lack of public knowledge about hypertension and information about drugs is an obstacle to success in the healing process. In line with this, Gebriet et al. (2017) explained that the level of knowledge and understanding of hypertensive patients regarding their disease can support the success of therapy so that the patient's blood pressure can be well controlled. The more patients understand their disease, the more aware patients will be in maintaining a lifestyle, regularly taking medication, and the level of patient compliance will also increase. Before conducting counseling, participants were given a pre-test to find out how much knowledge the community had about hypertension. During the implementation of the activity, participants paid attention enthusiastically and actively. This can be seen from the many questions from the participants and the right answers to questions from the community service team. At the end of the activity, participants conducted an evaluation. The results of the evaluation conducted from 10 participants showed that the pre-test results were 45% good, 55% fair value, the post-test results showed that 85% good 15% fair. So there has been an increase in knowledge from before and after counseling.